The Role of GRIT as a Moderator of the Relationship Between Job Insecurity and Job Involvement for Employees Affected by Covid-19 - Dayatri, Nyimas Fathia; Salendu, Alice (Journal of Research and Measurement in Psychology: JPPP, 2022)
This study aims to determine the relationship between job insecurity and job involvement by considering the role of grit as the moderator in employees during the Covid-19 pandemic. Research respondents are 762 public and private sectors employees who work in organization which implemented policy changes due to Covid-19. This research is a quantitative study with a cross-sectional study design. The sampling technique used is accidental sampling. The research measuring instruments consists of Job Involvement Scale, Multidimensional Qualitative Job Insecurity Scale (MQJIS), and Short Grit Scale (Grit-S). Data were collected using an online questionnaire and analyzed using regression analysis, utilizing SPSS PROCESS Model 1. It was found that grit did not moderate the relationship between job insecurity and job involvement. As the implication, the findings of this research can be used by organizations as reference to anticipate the increase of employee job insecurity due to changes.